The Investigation of Serum Lipid Levels in Chronic Obstructive Pulmonary Disease and Asthmatic Patients - Deveci, Figen; Turgut, Teyfik; İlhan, Nevin; Muz, M.hamdi; Kırkıl, Gamze; Terzi, S. Murat (Fırat University, 2001)
There is not clear data about serum lipid levels in asthmatics in whom dietary intake is decreased, and stress factors and hypoxemia are present. The malnutrition was determined in 20% of stable COPD patients. In our study, these two diseases, which affect effort capacity and nutrition, were compared with healthy individuals. The patients who were asthmatics (35), who had stable COPD (41) and healthy individuals (30) were included in the study. Cholesterol, TG, HDL-C, LDL-C, VLDL- C were measured in patients and control groups. Serum LDL-C levels were significantly decreased in COPD versus to control groups (p

Diyet alınımının azalması, stres faktörlerinin varlığı ve hipoksemi gibi pek çok faktörün mevcut olduğu astmada serum lipid düzeyleri konusunda net bilgiler mevcut değildir. Stabil KOAH'lı hastaların yaklaşık %20' sinde, malnutrisyon mevcut olduğu saptanmıştır. Çalışmamızda kronik inflamasyonla seyreden, hipokseminin eşlik ettiği, beslenme ve efor kapasitelerini etkileyen bu iki hastalık grubundaki serum lipid düzeyleri normal kişilerle kıyaslanarak araştırılmıştır. 35 astmalı, 41 stabil KOAH'lı ve 30 sağlıklı kişi çalışma kapsamına alındı. Hasta ve kontrol grubunun kolesterol, trigliserid, HDL-kolesterol (HDL-C), LDL-kolesterol (LDL-C), VLDL-kolesterol (VLDL-C) düzeyleri ölçüldü. Serum LDL-C düzeyleri KOAH'lılarda kontrol grubuna göre anlamlı düşük bulundu (p
KRONİK OBSTRÜKTİF AKCİĞER HASTALIKLI VE ASTMALI HASTALARDA SERUM LİPİD DÜZEYLERİNİN İNCELENMESİ